Population genetic analysis of clinical Mycobacterium abscessus complex strains in China - Li, Xiangchen; Zhu, Yelei; Lu, Yewei; Wu, Kunyang; Che, Yang; Wang, Xiaomeng; Wang, Weixin; Gao, Junli; Gao, Junshun; Liu, Zhengwei; Zhou, Zhuxian (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundTo explore the genetic characteristics of the Mycobacterium abscessus complex (MABC) population in China, given its rising clinical importance among nontuberculous mycobacteria.MethodsWe conducted population genetic analyses on 360 MABC genomes from China, focusing on core genome multilocus sequence typing (cgMLST), pan-genome characterization, population genetics, and antimicrobial resistance gene profiling.ResultsOur analysis identified 273 M. abscessus subsp. abscessus (MabA) and 87 M. abscessus subsp. massiliense (MabM) isolates, uncovering 68 sequence types (STs), with ST5 being the most common. cgMLST classified 33.3% of isolates into six dominant circulating clones (DCCs) and 49.4% into 59 genomic clusters at a threshold of 25 different alleles, including 18 international clusters linking Chinese isolates with seven other countries. The MABC pan-genome is open, with MabA exhibiting greater accessory gene diversity and higher gene turnover compared to MabM. Mobile genetic elements (MGEs), such as prophages and genomic islands, were prevalent across all genomes. 139 to 151 virulence factors (VFs) were identified per genome, with distinct accessory VFs in MabA and MabM affecting immune modulation and metabolism. Resistance gene profiling revealed ubiquitous mtrA, RbpA, and blaMAB, with MabA-specific erm(41) conferring resistance to macrolides and β-lactams. Common rrs and rrl gene mutations indicated widespread resistance to aminoglycosides and macrolides, while gyrA mutations suggested emerging fluoroquinolone resistance. An acquired erm(46) gene, likely obtained via phage-mediated horizontal gene transfer, was detected in one MabA strain.ConclusionThis study provides key genetic insights into the dynamics of MABC in China. The widespread distribution of DCCs, high genomic clustering rates, open pan-genome, and distinct resistance patterns between MabA and MabM, along with MGEs, highlight the need for targeted surveillance and tailored therapies to address emerging challenges in MABC infections.